2009
DOI: 10.1016/j.ejvs.2008.12.018
|View full text |Cite
|
Sign up to set email alerts
|

Early Carotid Endarterectomy after Intravenous Thrombolysis for Acute Ischaemic Stroke

Abstract: In patients with residual cervical ICA stenosis after IVT, we achieved full patency of the occluded artery and good functional prognosis at 3 months in all cases. We advocate for an extremely close monitoring of the blood pressure in the pre-, peri- and post-operative course and a close collaboration between neurologist and surgeon to determine the best timing for CEA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
31
0
4

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 26 publications
1
31
0
4
Order By: Relevance
“…Consistent with this, another report by Rathenborg et al 11 also found that thrombolysis did not seem to increase the risk of serious complications in patients undergoing subsequent CEA, although a slightly higher bleeding complication rate (9%) was reported. Bartoli et al 12 also reported favorable outcomes of CEA undertaken on a median time of 8 days after thrombolysis; however, unlike the above authors, this group did report 1 hemorrhagic stroke that resulted in death. Finally, in a small series published recently consisting of 7 patients undergoing CEA after successful thrombolysis, 13 there was 1 postoperative intracranial hemorrhage but no other complications at 30 days.…”
Section: Discussionmentioning
confidence: 58%
“…Consistent with this, another report by Rathenborg et al 11 also found that thrombolysis did not seem to increase the risk of serious complications in patients undergoing subsequent CEA, although a slightly higher bleeding complication rate (9%) was reported. Bartoli et al 12 also reported favorable outcomes of CEA undertaken on a median time of 8 days after thrombolysis; however, unlike the above authors, this group did report 1 hemorrhagic stroke that resulted in death. Finally, in a small series published recently consisting of 7 patients undergoing CEA after successful thrombolysis, 13 there was 1 postoperative intracranial hemorrhage but no other complications at 30 days.…”
Section: Discussionmentioning
confidence: 58%
“…A similar series from Marseilles, France, described one major adverse neurological event after acute CEA: a haemorrhagic stroke 6 . The present series differed in that the majority of patients had treatment under local anaesthesia.…”
Section: Discussionmentioning
confidence: 98%
“…The present series differed in that the majority of patients had treatment under local anaesthesia. Similarly, only 6 per cent of patients who had stroke thrombolysis were suitable for CEA in Marseilles 6 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Yet, with the increasing number of stroke units, the question of a rapid revascularization of residual ICA stenosis after thrombolysis has emerged. Recent studies reported reassuring results but they were small population studies [25][26][27][28].Among the two neurological complications in our study, one was a postoperative stroke after thrombolysis and delayed CR. We believe early CR after thrombolysis should be considered, but larger series of patients are required to con irm the safety of such management.…”
Section: Discussionmentioning
confidence: 74%